2001
DOI: 10.1021/jo0103726
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Rotation in Methyl Formate by Dynamic NMR Spectroscopy and Barriers to 1,3 Oxygen-to-Oxygen Migration in Methyl Formate and Trifluoromethyl Formate by ab Initio Calculations

Abstract: Free-energy barriers of 9.85 and 11.91 +/- 0.15 kcal/mol at -70.8 degrees C were found by dynamic NMR spectroscopy for the E-to-Z and Z-to-E conversions, respectively, of methyl formate (1) enriched in 13C to 99% for the carbonyl carbon [methyl formate 13C (2)]. These barriers are higher than the literature values reported for -53 degrees C. The free-energy barrier to 1,3 oxygen-to-oxygen migration of the methyl group in methyl formate was determined by ab initio calculations at several levels. The value of 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…[1] Free-energy barriers of 9.85 and 11.91 kcal/mol have been reported [2] for the E-to-Z and Z-to-E conversions of methyl formate at -70.8°C, and the population of the E isomer was only 0.006 at this temperature in a favorable (polar) solvent. The Z-conformation is generally favored over the E-conformation, due in part to destabilization of the E isomers by dipole-dipole interactions, as reflected in their higher dipole moments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Free-energy barriers of 9.85 and 11.91 kcal/mol have been reported [2] for the E-to-Z and Z-to-E conversions of methyl formate at -70.8°C, and the population of the E isomer was only 0.006 at this temperature in a favorable (polar) solvent. The Z-conformation is generally favored over the E-conformation, due in part to destabilization of the E isomers by dipole-dipole interactions, as reflected in their higher dipole moments.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Free-energy barriers of 9.85 and 11.91 kcal/mol have been reported [2] for the E-to-Z and Z-to-E conversions of methyl formate at -70.8°C, and the population of the E isomer was only 0.006 at this temperature in a favorable (polar) solvent. Populations were estimated at the coalescence temperature of -151.9°C for the carbonyl carbon atoms, and rate constants of 172.1 and 141.1 s -1 were obtained by lineshape matching.…”
mentioning
confidence: 99%
“…The conformation of esters has been the subject of essential investigation from a very long back, revealing that the Z conformations of most esters are strongly favoured [1][2][3] by both steric interactions and dipole-dipole interactions over the E conformations ( Figure 1). But it was also observed that in formate esters, the steric repulsion in E-conformer between the formyl hydrogen and R' will be smaller than the repulsion in the Z-conformations between the carbonyl oxygen and R', and the E-conformer will be favoured 3 by steric effects, although, such effects favour the E-conformers in these esters of formic acid, the Z-conformers have larger population due to other factors including more favourable dipole-dipole interactions.…”
Section: Introductionmentioning
confidence: 99%
“…But it was also observed that in formate esters, the steric repulsion in E-conformer between the formyl hydrogen and R' will be smaller than the repulsion in the Z-conformations between the carbonyl oxygen and R', and the E-conformer will be favoured 3 by steric effects, although, such effects favour the E-conformers in these esters of formic acid, the Z-conformers have larger population due to other factors including more favourable dipole-dipole interactions. It has been reported that compounds with Csp 2 -Csp 2 bonds possess some double bond character 4 as they belong to conjugated systems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, contrary to the IMDA reaction of hydrocarbon substrates or amide-tethered triene compounds, that of ester tethered substrates generally requires high temperature and long reaction time to get the cyclized product, but in some cases even fails to obtain any cyclized product [9][10][11][12][13][14]. The low reactivity of ester tethered substrate is explained by a preference of transoid geometry due to repulsive dipole interaction between carbonyl-oxygen and ethereal oxygen and steric repulsion between two alkyl substituents (R 1 and R 2 ), thereby the cisoid form, in which the diene and dienophile are in close proximity required for the IMDA reaction is more unfavorable [15][16][17][18][19][20]. Towards to this issue, we have demonstrated that a bidentate Lewis acid, which has bis-aluminated triflic amide structure, can nicely promote the IMDA reaction of ester tethered 1,7,9-decatrienoates [21][22][23].…”
Section: Introductionmentioning
confidence: 99%